Digital Transformation of Villages with Local Wisdom: A Preventive Legal Instrument Against Maladministration Practices of Village Head Positions - Haizul Ma'arif; Suhadi Suhadi (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This research is based on the phenomenon of maladministration practices in the position of Village Head in Jepara Regency, including service delays and illegal levies, which hinder development and infringe on residents' constitutional rights. The urgency of this research lies in the need for digital transformation as a preventive legal instrument to mitigate the risk of abuse of authority through transparency and systemic accountability. The method used in this study is a quantitative approach using path analysis, complemented by the examination of regional regulations, such as the Jepara Regent Regulation on the Electronic-Based Government System (SPBE), and case studies in Rajekwesi Village. The results of the study show that the implementation of e-Government through the Village Information System (SID) and Siskeudes significantly improves the integrity of village leadership in preventing corruption. In addition to the technological aspect, the value of Jepara's local wisdom, especially the philosophy of Ratu Kalinyamat, has proven effective in moderating the relationship between the digital system and leaders' personal honesty. The conclusion of the study emphasizes that the synergy between strict regional regulations, the standardization of digital procedures, and the internalization of cultural ethics is a fundamental strategy for realizing clean, service-oriented village governance.